Bone Health and Natural Products- An Insight - Suvarna, Vasanti; Sarkar, Megha; Chaubey, Pramila; Khan, Tabassum; Sherje, Atul; Patel, Kavitkumar; Dravyakar, Bhushan (Frontiers in Pharmacology, 2018)
Bone metabolism involves a complex balance between matrix deposition, mineralization and resorption. Numerous evidences have revealed that dietary components and phytoconstituents can influence these processes, through inhibition of bone resorption, thus exhibiting beneficial effects on the skeleton. Various traditional herbal formulae in ayurvedic and Chinese medicine have shown demonstrable benefits in pharmacological models of osteoporosis. The present review discusses normal bone metabolism and disorders caused by bone disruption, with particular reference to osteoporosis and current therapeutic treatment. Furthermore the effects of constituents from natural products on bone tissue are explained, with relevant evidences of efficacy in various experimental models.